2012
DOI: 10.1159/000337373
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Fraction in Maternal Plasma Cell-Free DNA at 11–13 Weeks’ Gestation: Effect of Maternal and Fetal Factors

Abstract: Objective: It was the aim of this study to examine the possible effects of maternal and fetal characteristics on the fetal fraction in maternal plasma cell-free DNA (cfDNA) at 11–13 weeks’ gestation. Methods: In a nested case-control study, cfDNA was extracted from maternal plasma obtained before chorionic villous sampling from 300 euploid, 50 trisomy 21 and 50 trisomy 18 pregnancies at 11–13 weeks’ gestation. Chromosome-selective sequencing of maternal cfDNA non-polymorphic and polymorphic loci, where fetal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
107
6
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(136 citation statements)
references
References 64 publications
17
107
6
6
Order By: Relevance
“…Furthermore, it has been reported that discordant results can be due to variations in the maternal DNA contribution, including low-level sex chromosome and autosomal chromosome mosaicism, maternal malignancies, and maternal copynumber variants. 9,17,[25][26][27] It is well known that some women may have low-level age-related losses and gains of the X chromosome. 28,29 There are a few reports of concurrent maternal malignancies when multiple or rare aneuploidies (e.g., autosomal monosomies) are detected by NIPS.…”
Section: Sources Of Discordant Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been reported that discordant results can be due to variations in the maternal DNA contribution, including low-level sex chromosome and autosomal chromosome mosaicism, maternal malignancies, and maternal copynumber variants. 9,17,[25][26][27] It is well known that some women may have low-level age-related losses and gains of the X chromosome. 28,29 There are a few reports of concurrent maternal malignancies when multiple or rare aneuploidies (e.g., autosomal monosomies) are detected by NIPS.…”
Section: Sources Of Discordant Resultsmentioning
confidence: 99%
“…[13][14][15][16] While NIPS can be performed in the late first trimester of pregnancy, and CVS is a possibility for confirmatory studies (and often desired by the patient due to timing), CVS may simply reflect the same DNA/cells that were detected by NIPS, as both are derived from the placenta. 17 Certain aneuploidies, including trisomy 13 and monosomy X, are more likely to be found in the mosaic form on CVS, which may influence genetic counseling about the preferred diagnostic test for confirmatory studies. 18 When CVS shows mosaicism for the suspected trisomy, it is impossible to determine if this is CPM or true fetal mosaicism (TFM).…”
Section: Diagnostic Testingmentioning
confidence: 99%
“…The fetal fraction is significantly lower in overweight mothers and is increased in cases with high levels of free beta-hCG and PAPP-A. It is not significantly related to maternal age, storage time, smoking status, nuchal translucency thickness, fetal crown-rump length, gender or karyotype (12). In his study Nicolaides KH et al found that the fetal fraction declines from a mean of about 12% at a 60 kg maternal weight to as low as 6% at 120 kg.…”
Section: Course Notesmentioning
confidence: 87%
“…The cffDNA represents on average 6%-10% of the total cfDNA in first-and second-trimester pregnancies, and increases to 10%-20% in third-trimester pregnancies (2,3 ). However, the fetal fraction can remain Ͻ4% in the first trimester (4,5 ). To conclude whether a negative result of an NIPD assay is a true or false negative, a marker to confirm the presence of fetal nucleic acids (a fetal marker) is crucial.…”
mentioning
confidence: 99%
“…To date, in general, 2 methods are used to confirm that cffDNA is present in the sample. The first is the detection of paternally inherited alleles (17 ), and the second is the amplification of hypermethylated placental genes, such as RASSF1A [Ras association (RalGDS/AF-6) domain family member 1, isoform A], 5 after removing maternal unmethylated gene sequences by a methylationsensitive endonuclease (18 ). Both approaches have drawbacks.…”
mentioning
confidence: 99%